The Impact of Public Subsidies on Venture Capital Investments in Start-Up Enterprises - Andrea Schertler (Kiel Institute of World Economics (IfW), 2000)
The relationship between a venture capitalist and an entrepreneur is modeled to investigate the impact of public subsidies on venture capital investments in start-up enterprises. In this model, the venture capitalist only finances start-up enterprises if he has sufficient expertise to make high-risk investments in new technology profitable in terms of their expected value. It is shown that a venture capitalist who already has sufficient expertise reduces his management support in the start-up enterprise under a public subsidy. Moreover, venture capitalists who do not have sufficient expertise may finance start-up enterprises if future losses of the start-up investment are partly covered by the government.
Keywords: L14; G28; G24; D82; 330; venture capital; double-sided moral hazard; public subsidies; start-up investments; Risikokapital; Unternehmensgründung; Investition; Finanzierung; Investitionspolitik; Subvention; Moral Hazard; Theorie